During the Audit Process, The Main Means of Composition, Structure and Methods of Technical Condition Analysis - A. Mamajonov; R. Khabibullaeva (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the authors discussed the methods of analyzing the composition, structure and technical condition of the main tools during the audit process.